2022
DOI: 10.5334/gh.1106
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Closure of Perimembranous Ventricular Septal Defect Using the Lifetech Konar-Multi Functional Occluder: Early to Midterm Results of the Indonesian Multicenter Study

Abstract: Background:The alternative device to close perimembranous ventricular septal defect (pmVSD) has been searched for better result, less complications and applicable for infants. However, the ideal device is still unavailable. We aimed to evaluate the effectiveness and outcome of transcatheter pmVSD closure using the KONAR-multi functional occluder (MFO).Methods: Clinical, procedural, follow-up data of pmVSD patients with symptom of heart failure or evidence of significant left to right shunt, growth failure, rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
0
13
1
Order By: Relevance
“…Unlike the AMPLATZER Membranous Occluder, the AMPLATZER Duct Occluder II (Abbott Laboratories) and the KONAR-MF multifunctional occluder (Lifetech Scientific) have shown less risk of AVB. 13 , 14 In our subjects, there were no reports of LBBB during follow-up, and 1 patient with complete RBBB at postoperative month 1 converted to normal status at month 6. If AVB or complete LBBB develop during or after procedures, we mandate occluder extraction as soon as feasible, especially in pediatric patients.…”
Section: Discussionmentioning
confidence: 62%
“…Unlike the AMPLATZER Membranous Occluder, the AMPLATZER Duct Occluder II (Abbott Laboratories) and the KONAR-MF multifunctional occluder (Lifetech Scientific) have shown less risk of AVB. 13 , 14 In our subjects, there were no reports of LBBB during follow-up, and 1 patient with complete RBBB at postoperative month 1 converted to normal status at month 6. If AVB or complete LBBB develop during or after procedures, we mandate occluder extraction as soon as feasible, especially in pediatric patients.…”
Section: Discussionmentioning
confidence: 62%
“…For all large (>6 mm) defects and cases with SAR < 3 mm, MFO was employed to prevent embolization and the development of insufficiency in the aortic and tricuspid valves. Both devices, with their soft profiles and small delivery sheaths, allow for retrograde or antegrade approaches during implantation ( 21 , 22 ). The ability to be screwed from both sides facilitates the positioning and manipulation of the discs without anatomical constriction on the right side, particularly in pmVSDs with wide and aneurysmal tissue, making the MFO device advantageous compared to ADOII ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The su cient distance between the defect and the aortic valve is essential to avoid aortic regurgitation [8,29]. The ideal distance from the defect to the aortic valve using the Lifetech Konar-MF device is more than 2 mm [20,30]. A small number of studies reported that pmVSD without aneurysm is di cult to be treated with the Lifetech Konar-MF device as the symmetrical discs might injure the aortic valve [20].…”
Section: Discussionmentioning
confidence: 99%